2004
DOI: 10.1002/app.20905
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity and oxygen transport properties of PET bottle walls

Abstract: ABSTRACT:Oxygen transport was coupled with other methods to study the relationship of gas barrier to solid state structure in the PET blown bottle wall. Commercial 2-L carbonated soft drink bottles blown under different process conditions were studied. Crystallinity determinations from heat of melting, density, glycol trans fraction, and oxygen solubility were compared. The reasons for lack of correlation between conventional crystallinity methods based on heat of melting and density were elucidated, and neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 25 publications
3
46
0
1
Order By: Relevance
“…They attribute the dedensification to increased constraints on the amorphous phase macromolecular chains due to their attachment to crystallites. This effect causes the glass transition to shift to higher temperatures [40], which is also observed in our case and in the case of Drieskens' publication for PLA. In the case of PLA the shift of the T g was attributed to the confinement of the MAF, though [21][22][23][24], as the RAF is not able to relax in the region of the glass transition.…”
Section: Gas Barrier Propertiessupporting
confidence: 85%
See 1 more Smart Citation
“…They attribute the dedensification to increased constraints on the amorphous phase macromolecular chains due to their attachment to crystallites. This effect causes the glass transition to shift to higher temperatures [40], which is also observed in our case and in the case of Drieskens' publication for PLA. In the case of PLA the shift of the T g was attributed to the confinement of the MAF, though [21][22][23][24], as the RAF is not able to relax in the region of the glass transition.…”
Section: Gas Barrier Propertiessupporting
confidence: 85%
“…In the case of poly(ethylene terephthalate) (PET), permeability decrease with increasing crystallinity only relies on the drop of D and a rise of S what has been evidenced by several authors [38][39][40]. The effect was explained by dedensification of the amorphous phase, which increases oxygen solubility.…”
Section: Gas Barrier Propertiesmentioning
confidence: 92%
“…Analogous phenomena occur in PET, and the competing effects of simultaneous orientation and crystallization are manifest in the blown bottle wall. 59 The dedensification of the amorphous phase can be discussed in terms of the temperature-volume relationship in Figure 5. 58 As the polymer is cooled from the melt, unconstrained amorphous chains contract along the equilibrium liquid line to the glass transition and then along the solid line to 25°C.…”
Section: Crystalline Polyesters Oxygen Solubility and Glassy Amorphoumentioning
confidence: 99%
“…32 A second hypothesis might be the de-densification of the amorphous phase which counteracts the decrease of the quantity of permeable amorphous phase due to crystallization. Dedensification of the amorphous phase in PET has been shown by Liu et al 36 to be responsible for the higher oxygen permeability of bottle walls processed under conditions of higher thermal exposure, although the treatment led to an increase in the volume fraction of impermeable crystals. A decrease in the permeable amorphous phase density causing an increase of gas permeability through heat-set PET was also shown by Qureshi et al 37 It has been shown for poly(L-lactic acid) (PLLA), in comparison to PET, that there is an important decoupling between crystalline and surrounding amorphous phase.…”
Section: Gas Barrier Propertiesmentioning
confidence: 99%